Economía de plantación en Cuba (XVI-XIX): el problema de la mano de obra. (Estudio de antropología económica) - Fernández Álvarez, Oscar (Estudios humanísticos. Geografía, historia y arte, 1995)
Spanish poeple arrived at Cuba with treir own sketch of economic and politic organization, so that reproduced social relations prevailing in Europe. Immediately there's an effort for chaning indian agriculture in growing ocupation assigned subsistence of colinizer. Our purpose in this paper is to illustrate the freak of how the increase of slave people was entailed to the planting of sugar economy. At the end of XVI, a long succession of processes worked to make a sugar industry in Cuba, that'd karked their historic trace.